SISTEMA GERENCIADOR DE INFORMAÇÕES PARA A SÍNTESE DE NANOTUBOS DE CARBONO - Shibata, Henrique Yanaguibashi (2011)
The nanotecnology is an area with high growth in research, which covers many areas of knowledge and works with nanometers scale structures (10-9m). The applications are so diverse like the cure of diseases, resistant materials, computer processors and others one. Carbon nanotubes (CNT) are on eminence in this area and have been explored in researches due to their physical, chemical, magnetic and mechanical properties. These properties make possible a large numbers of applications in health, material, computer, electronic and technology fields. Because of it, the synthesis of CNT took an extreme importance. The main methods of production of CNT are: arc discharge, laser ablation and chemical deposition methods (CVD). The objectives of this paper were to build a database of CVD‟s synthesis parameters and the implementation and customization of web pages using a CMS (Content Management System) tool to show and collect information by web. This work presents an interdisciplinary character for the interaction between the computer, materials and chemistry fields. The quality of CNT synthesizes depends on parameters like catalyst, hydrocarbon, growth temperature, time of synthesis and inert atmosphere. The portal would help to access in orderly manner to the information, providing researches or people, which are interest in this subject, to start future studies about the production of this nanomaterial.